Kesetiaan dalam Pernikahan sebagai Karakteristik Seorang Pemimpin Kristen [Fidelity in Marriage as a Characteristic of a Christian Leader] - Novel Priyatna (Universitas Pelita Harapan, 2022)
Being the husband of a wife is one of the requirements set by Paul for an church overseer. However, there are various interpretations of Paul's words written in 1 Timothy 3:2a. The purpose of this article is to dig deeper into what Paul meant when he set out this requirement and how it relates to Christian leadership. For Paul, a Christian leader must be someone who has good credibility, namely as a husband who is faithful to his wife in a monogamous marriage. This is a manifestation of his faithfulness to God Himself. By having this qualification, a Christian leader can be a good example to his congregation.BAHASA INDONESIA ABSTRACT: Suami dari satu isteri merupakan salah satu persyaratan yang ditetapkan oleh Paulus bagi seorang penilik jemaat. Namun demikian, terdapat berbagai macam interpretasi atas perkataan Paulus yang tertulis didalam 1 Timotius 3:2a. Tujuan artikel ini adalah untuk menggali lebih dalam apa yang Paulus maksudkan ketika ia menetapkan persyaratan tersebut dan bagaimana relevansinya terhadap kepemimpinan Kristen. Bagi Paulus, seorang pemimpin Kristen haruslah seseorang yang memiliki kredibilitas yang baik, yaitu sebagai suami yang setia kepada istrinya dalam pernikahan monogami. Hal ini sebagai perwujudan dari kesetiaannya kepada Allah sendiri. Dengan memiliki kualifikasi tersebut, seorang pemimpin Kristen dapat menjadi teladan yang baik bagi jemaatnya.